PENGARUH FDI, PERDAGANGAN INTERNASIONAL TERHADAP EMISI CO2 ERA REVOLUSI INDUSTRI 4.0 - Qonita Rosyida Afifah; Kurniawan Ali Fachrudin; Alia Ariesanti (JIDE : Journal Of International Development Economics, 2024)
The Industrial Revolution 4.0 is characterized by increasingly advanced technologies that have developed globally, including the widespread use of online communication and digital-based economic activities. The development of trade in the Industrial Revolution 4.0 era has led to an increase in the volume and complexity of economic transactions. This condition has the potential to increase production activities, energy consumption, and trade mobility, which may subsequently contribute to higher carbon emissions and environm ental degradation. This study aims to analyze the effects FDI, exports, imports, industrial growth, and energy consumption on carbon dioxide (CO?) emissions. The study employs secondary data obtained from the World Bank and Our World in Data, using panel data covering the period from 2011 to 2023. The analytical method applied is panel data regression. The results that FDI has a positive and significant effect on CO? emissions. Meanwhile, exports, imports, and industrial growth do not have a significant effect on CO? emissions. In contrast, energy cons umption has a negative & significant effect on CO? emissions, FDI & energy are important factors that should be consider ed in efforts to control carbon emissions & promote environmental sustainability.